Local structure around In atoms in coherently grown m-plane InGaN film - Miyanaga, Takafumi (Journal of synchrotron radiation, 2017)
The local structure around In atoms in an m-plane In0.06Ga0.94N film coherently grown on a freestanding m-plane GaN substrate was investigated by polarization-dependent X-ray absorption fine-structure. A step-by-step fitting procedure was proposed for the m-plane wurtzite structure. The interatomic distance for the first nearest neighbour In-N atomic pairs was almost isotropic. For the second nearest In-Ga pairs, the interatomic distances along the m- and a-axes were longer and shorter, respectively, than that in strain-free virtual crystals as expected for the m-plane compressive strain. In contrast, the In-Ga interatomic distance in the c-direction was elongated in spite of the compressive strain, which was explained in terms of the anisotropic atomic structure on the m-plane. The local strain in the m-plane film was more relaxed than that in coherently grown c-plane single quantum wells. A few In atoms were atomically localized in all directions, and thus localized excitonic emission is expected as in the case of c-plane InGaN